Transformasi Kuda Lumping Dari Ritual Tradisional Menuju Atraksi Wisata Berkelanjutan Di Desa Wisata Mekarlaksana - Vani Yuniastoeti; Gitasiswhara (PURBAWIDYA, 2026)
This study examines how Kuda Lumping has transformed from a traditional ritual into a sustainable tourism attraction in Mekarlaksana Tourism Village, Bandung Regency. The commercialization of traditional performing arts creates a dilemma between preserving authenticity and meeting economic needs. Research objectives are to describe Kuda Lumping's characteristics and philosophical values, analyze its role in sustainable tourism, identify transformation challenges, and formulate development strategies. The study employs a descriptive qualitative approach with participant observation, in-depth interviews, and documentation. Data analysis uses Miles and Huberman's model. Findings indicate Kuda Lumping transformed from a sacred communal ritual into a scheduled tourism attraction while maintaining spiritual elements such as opening rituals, the pawang's role, and authentic trance phenomena. The transformation contributes positively to three sustainability pillars: economic (increased income and MSME multiplier effects), socio-cultural (strengthened local identity and intergenerational knowledge transfer), and environmental (eco-friendly materials). Major challenges include the authenticity versus commodification dilemma, declining youth interest, infrastructure limitations, and mystical controversies. Recommended strategies include sacred-profane balance principles, elder councils as guardians of tradition, educational approaches, and community-based decision making. The research confirms that traditional performing arts transformation can support tourism village sustainability through participatory principles, respecting local values, and balancing economic, cultural, and environmental interests.